Polyamide-imide composite nanofiber and preparation method thereof
By using wet spinning process and Si-O-Si structure in functional monomers in the textile field, polyamide imide composite nanofibers are prepared, which solves the problem of insufficient fiber flexibility, achieves higher mechanical properties and heat resistance, and is suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202510329965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The application of polyamide-imide fiber in the textile field is limited by the problem of poor flexibility, which makes clothes easily damaged after wearing at high temperatures and difficult to restore their initial state.
Polyamide imide composite nanofibers were prepared by using wet spinning process, using dianhydride monomer, diamine monomer and functional monomer as the main synthetic raw materials. The Si-O-Si structure is introduced into the functional monomer to improve the toughness of the fibers and improve the heat resistance of the fibers through oxidative cross-linking reaction.
It improves the flexibility, mechanical properties and heat resistance of the fiber, so that it can remain stable at high temperatures, and is suitable for a variety of high-performance applications, such as high-temperature filtration, protective clothing, aerospace, etc.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spinning fibers, and in particular to a polyamide-imide composite nanofiber and a preparation method thereof. Background Art
[0002] Polyamide-imide fiber (PAI fiber for short) is a high-performance fiber. The PAI molecular chain contains both relatively flexible amide groups and heat-resistant imide units. It has excellent mechanical properties and chemical stability and shows its unique advantages in many demanding applications. Therefore, this type of polymer not only has the excellent heat stability, low constant and dielectric loss, good mechanical properties, creep resistance, radiation resistance and solvent corrosion resistance of polyimide, but also has the excellent mechanical properties and processability of aromatic polyamide. It has a wide range of applications in the fields of aviation and aerospace industry, electrical and electronic industry, high-temperature cables, automotive industry, high-temperature filtration and marine engineering.
[0003] However, this type of polymer has a large number of rigid benzene ring structures in its molecular chain, which will cause the fiber material synthesized by the spinning process to have poor toughness, which limits the application of fiber materials in certain fields, such as in the textile field. Polyamide-imide has a unique macromolecular chain structure that makes PAI fiber and its fabrics not melt or continue to burn at high temperatures, and has excellent flame retardancy. It is widely used in protective clothing such as fire suits and anti-riot police uniforms. However, this type of fabric has poor flexibility and will cause damage to the clothes after long-term wearing, making it difficult to restore to its original state. Therefore, it is necessary to improve the toughness of PAI fiber through modification to meet actual needs. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a polyamide-imide composite nanofiber and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing polyamide-imide composite nanofibers comprises the following steps: Step S1, mixing and stirring the dianhydride monomer, the diamine monomer and the functional monomer in an organic solvent, and maintaining the temperature at 0° C. for reaction for 5-6 hours to obtain a polyamide-amic acid solution; Step S2, adding acetic anhydride and triethylamine to the above polyamide-amic acid solution and stirring well, reacting at 25-35°C for 4-6h, and then subjecting to vacuum degassing and filtering treatment, spraying out through a spinneret and entering a treatment liquid to obtain primary fibers, and then subjecting to a coagulation bath, hot water drawing, water washing, drying, thermal cyclization, and winding to obtain polyamide-imide composite nanofibers; Further, in step S1, the molar ratio of the dianhydride monomer, the diamine monomer and the functional monomer is 1:0.96-1:0.02-0.05, and the solid content of the polyamide-amic acid solution is 15%-25%; Furthermore, the dianhydride monomer in step S1 is one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride or 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; Furthermore, the diamine monomer in step S1 is one of p-phenylenediamine or diphenyl ether diamine; Furthermore, the organic solvent in step S1 is one of N,N-dimethylformamide or N,N-dimethylacetamide; Furthermore, the volume ratio of acetic anhydride and triethylamine in step S2 is 2-3:1, and the molar ratio of acetic anhydride and the dianhydride monomer in step S1 is 0.3-0.5:1; Furthermore, the treatment liquid in step S2 is a mixture of acetic anhydride and triethylamine in a volume ratio of 1:3; Furthermore, the coagulation bath in step S2 is a mixture of N,N-dimethylacetamide and water in a volume ratio of 4:6; Furthermore, in step S2, the hot water drawing temperature is 90°C, the drawing ratio is 2.4, and the thermal cyclization temperature is 320°C.
[0006] The functional monomer is prepared by the following steps: Step A1, stir p-nitrobenzoyl chloride in tetrahydrofuran, transfer to an ice-water bath, add pyridine and stir for 1 hour, then add 1-amino-5-hexene and stir for 3.5-4.5 hours, add water and stir for 30 minutes, filter, recrystallize and dry to obtain a nitro-benzamide derivative; Further, in step A1, the usage ratio of p-nitrobenzoyl chloride, tetrahydrofuran, 1-amino-5-hexene, pyridine and water is 0.01-0.03 mol:100 mL:0.01-0.03 mol:0.01-0.03 mol:200 mL; Step A2, stirring a nitro-benzamide derivative, ethanol and a catalyst Pt / SnO2-Sb2O3 at a constant temperature of 50°C for 15 minutes, then introducing 4MPa hydrogen, stirring for 3 hours, and extracting to obtain an amino-benzamide derivative; Further, in step A2, the ratio of the nitro-benzamide derivative, ethanol and the catalyst Pt / SnO2-Sb2O3 is 0.5-1.5 g:10-30 mL:0.3-0.9 g; Further, in step A2, in the catalyst Pt / SnO2-Sb2O3, Pt accounts for 0.5wt% of the total amount of the catalyst, and the molar ratio of Sn to Sb is 0.1:1; Step A3, toluene-2,4-diisocyanate, sodium hydroxide, toluene and amino-benzamide derivative are mixed, and the temperature is raised to 60-70° C., nitrogen is introduced to react for 10-15 hours, and rotary evaporation and drying are performed to obtain isocyanate-benzamide derivative; Further, in step A3, the ratio of toluene-2,4-diisocyanate, sodium hydroxide, toluene and amino-benzamide derivative is 0.01-0.02 mol: 0.02-0.04 g: 100 mL: 0.01-0.02 mol; Step A4, adding sodium hydroxide, toluene and ethylenediamine to the isocyanate-benzamide derivative, stirring evenly, reacting under nitrogen at 70° C. for 6-8 hours, rotary evaporation and drying to obtain a double bond-benzamide derivative; Further, in step A4, the molar ratio of ethylenediamine to toluene-2,4-diisocyanate in step A3 is 1:1, and the amount of sodium hydroxide used is 0.015-0.03 g; Step A5, under nitrogen conditions, the double bond-benzamide derivative, KARSTEDT catalyst and toluene are mixed and stirred evenly, and then hydrogen-terminated polydimethylsiloxane is slowly added dropwise, and the temperature is raised to 80-100° C. to react for 20-24 hours, and then rotary evaporated, purified and dried to obtain a functional monomer; Further, in step A5, the molar ratio of hydrogen-terminated polydimethylsiloxane to the double bond-benzamide derivative is 1:1-1.02, and the KARSTEDT catalyst accounts for 0.002wt% of the total reactants.
[0007] Another object of the present invention is to provide a polyamide-imide composite nanofiber prepared by the above method.
[0008] Beneficial effects of the present invention: The polyamide-imide composite nanofiber in the present application is synthesized by wet spinning process with dianhydride monomer, diamine monomer and functional monomer as main synthetic raw materials; the composite nanofiber not only combines the advantages of traditional polyamide fiber and polyimide fiber, but also improves the flexibility, mechanical properties and heat resistance of the fiber by introducing functional monomer. Therefore, the polyamide-imide composite nanofiber in the present invention has broad application prospects in the fields of high-temperature filtration, protective clothing, aerospace, electronic and electrical, automotive industry, industrial sealing, composite materials, medical materials and environmental protection materials.
[0009] When the functional monomers in the present application are used as raw materials to synthesize polyamide-imide fiber molecules, a Si-O-Si structure is introduced into the main chain thereof, which has excellent flexibility and can improve the toughness of the fiber, making it easier to process and use. At the same time, the Si-O-Si structure will undergo an oxidative cross-linking reaction at high temperatures, thereby increasing the cross-linking density of the polyamide-imide fiber. The increase in the cross-linking density enhances the interaction between the molecular chains of the fiber, thereby improving the heat resistance of the fiber and allowing it to remain stable at high temperatures. In addition, the introduction of urea bonds enhances the intermolecular forces of the fiber, improves the strength and toughness of the fiber, and can also utilize the benzene ring structure with large steric hindrance to protect it, thereby reducing the impact of high temperature on it. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0011] Example 1: The functional monomer is prepared by the following steps: Step A1, stir 0.01 mol of p-nitrobenzoyl chloride in 100 mL of tetrahydrofuran, transfer to an ice-water bath, add 0.01 mol of pyridine and stir for 1 h, then add 0.01 mol of 1-amino-5-hexene and stir for 3.5 h, add 200 mL of water and stir for 30 min, filter, recrystallize and dry to obtain a nitro-benzamide derivative; Step A2, 0.5 g of nitro-benzamide derivative, 10 mL of ethanol and 0.3 g of catalyst Pt / SnO2-Sb2O3 were stirred at a constant temperature of 50°C for 15 min, and then 4 MPa of hydrogen was introduced, stirred for 3 h, and extracted to obtain an amino-benzamide derivative, wherein Pt in the catalyst Pt / SnO2-Sb2O3 accounts for 0.5 wt% of the total amount of the catalyst, and the molar ratio of Sn to Sb is 0.1:1; Step A3, 0.01 mol toluene-2,4-diisocyanate, 0.02 g sodium hydroxide, 100 mL toluene and 0.01 mol amino-benzamide derivative are mixed, and the mixture is heated to 60° C., nitrogen is introduced to react for 10 h, and the mixture is rotary evaporated and dried to obtain an isocyanate-benzamide derivative; Step A4, adding sodium hydroxide, toluene and ethylenediamine to the isocyanate-benzamide derivative, stirring evenly, reacting under nitrogen at 70°C for 6 hours, rotary evaporation and drying to obtain a double bond-benzamide derivative, the molar ratio of ethylenediamine to toluene-2,4-diisocyanate in step A3 is 1:1, and the amount of sodium hydroxide used is 0.015 g; Step A5. Under nitrogen conditions, the double bond-benzamide derivative, KARSTEDT catalyst and toluene are mixed and stirred evenly, and then the hydrogen-terminated polydimethylsiloxane is slowly added dropwise, and the temperature is raised to 80°C to react for 20 hours. The functional monomer is obtained by rotary evaporation, purification and drying. The molar ratio of hydrogen-terminated polydimethylsiloxane to the double bond-benzamide derivative is 1:1, and the KARSTEDT catalyst accounts for 0.002wt% of the total reactants.
[0012] Example 2: Functional monomers are prepared by the following steps: Step A1, stir 0.02 mol of p-nitrobenzoyl chloride in 100 mL of tetrahydrofuran, transfer to an ice-water bath, add 0.02 mol of pyridine and stir for 1 h, then add 0.02 mol of 1-amino-5-hexene and stir for 4 h, add 200 mL of water and stir for 30 min, filter, recrystallize and dry to obtain a nitro-benzamide derivative; Step A2, 1 g of nitro-benzamide derivative, 20 mL of ethanol and 0.6 g of catalyst Pt / SnO2-Sb2O3 were stirred at a constant temperature of 50°C for 15 min, and then 4 MPa of hydrogen was introduced, stirred for 3 h, and extracted to obtain an amino-benzamide derivative, wherein Pt in the catalyst Pt / SnO2-Sb2O3 accounts for 0.5 wt% of the total amount of the catalyst, and the molar ratio of Sn to Sb is 0.1:1; Step A3, 0.015 mol of toluene-2,4-diisocyanate, 0.03 g of sodium hydroxide, 100 mL of toluene and 0.015 mol of an amino-benzamide derivative are mixed, and the mixture is heated to 65° C., nitrogen is introduced to react for 12 h, and the mixture is rotary evaporated and dried to obtain an isocyanate-benzamide derivative; Step A4, adding sodium hydroxide, toluene and ethylenediamine to the isocyanate-benzamide derivative, stirring evenly, reacting under nitrogen at 70°C for 7h, rotary evaporation and drying to obtain a double bond-benzamide derivative, the molar ratio of ethylenediamine to toluene-2,4-diisocyanate in step A3 is 1:1, and the amount of sodium hydroxide used is 0.022g; Step A5. Under nitrogen conditions, the double bond-benzamide derivative, KARSTEDT catalyst and toluene are mixed and stirred evenly, and then the hydrogen-terminated polydimethylsiloxane is slowly added dropwise, and the temperature is raised to 90°C for reaction for 22 hours. The functional monomer is obtained by rotary evaporation, purification and drying. The molar ratio of hydrogen-terminated polydimethylsiloxane to the double bond-benzamide derivative is 1:1.01, and the KARSTEDT catalyst accounts for 0.002wt% of the total reactants.
[0013] Example 3: Functional monomers are prepared by the following steps: Step A1, stir 0.03 mol of p-nitrobenzoyl chloride in 100 mL of tetrahydrofuran, transfer to an ice-water bath, add 0.03 mol of pyridine and stir for 1 h, then add 0.03 mol of 1-amino-5-hexene and stir for 4.5 h, add 200 mL of water and stir for 30 min, filter, recrystallize and dry to obtain a nitro-benzamide derivative; Step A2, 1.5 g of nitro-benzamide derivative, 30 mL of ethanol and 0.9 g of catalyst Pt / SnO2-Sb2O3 were stirred at a constant temperature of 50°C for 15 min, and then 4 MPa of hydrogen was introduced, stirred for 3 h, and extracted to obtain an amino-benzamide derivative, wherein Pt in the catalyst Pt / SnO2-Sb2O3 accounts for 0.5 wt% of the total amount of the catalyst, and the molar ratio of Sn to Sb is 0.1:1; Step A3, 0.02 mol toluene-2,4-diisocyanate, 0.04 g sodium hydroxide, 100 mL toluene and 0.02 mol amino-benzamide derivative were mixed, and the mixture was heated to 70° C., nitrogen was introduced to react for 15 h, and rotary evaporated and dried to obtain an isocyanate-benzamide derivative; Step A4, adding sodium hydroxide, toluene and ethylenediamine to the isocyanate-benzamide derivative, stirring evenly, reacting under nitrogen at 70°C for 8h, rotary evaporation and drying to obtain a double bond-benzamide derivative, the molar ratio of ethylenediamine to toluene-2,4-diisocyanate in step A3 is 1:1, and the amount of sodium hydroxide used is 0.03g; Step A5. Under nitrogen conditions, the double bond-benzamide derivative, KARSTEDT catalyst and toluene are mixed and stirred evenly, and then the hydrogen-terminated polydimethylsiloxane is slowly added dropwise, and the temperature is raised to 100°C for reaction for 24 hours. The functional monomer is obtained by rotary evaporation, purification and drying. The molar ratio of hydrogen-terminated polydimethylsiloxane to the double bond-benzamide derivative is 1:1.02, and the KARSTEDT catalyst accounts for 0.002wt% of the total reactants.
[0014] Embodiment 4: A method for preparing polyamide-imide composite nanofibers, comprising the following steps: Step S1, mixing 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, p-phenylenediamine and the functional monomer prepared in Example 1 in N,N-dimethylformamide, and keeping the temperature at 0°C for reaction for 5 hours to obtain a polyamide-amic acid solution, wherein the molar ratio of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, p-phenylenediamine and the functional monomer prepared in Example 1 is 1:1:0.02, and the solid content of the polyamide-amic acid solution is 15%; Step S2, add acetic anhydride and triethylamine to the above-mentioned polyamide-amic acid solution and stir well, react at 25°C for 4h, and then after vacuum degassing and filtration treatment, spray out through a spinneret and enter the treatment liquid to obtain primary fibers, and then pass through a coagulation bath, hot water drawing, water washing, drying, thermal cyclization, and winding to obtain polyamide-imide composite nanofibers. The volume ratio of acetic anhydride and triethylamine is 2:1, and the molar ratio of acetic anhydride to the dianhydride monomer described in step S1 is 0.3:1. The treatment liquid is a mixed solution of acetic anhydride and triethylamine with a volume ratio of 1:3, and the coagulation bath is a mixed solution of N,N-dimethylacetamide and water with a volume ratio of 4:6. The hot water drawing temperature is 90°C, the drawing multiple is 2.4, and the thermal cyclization temperature is 320°C.
[0015] Embodiment 5: A method for preparing polyamide-imide composite nanofibers, comprising the following steps: Step S1, mixing pyromellitic anhydride, diphenyl ether diamine and the functional monomer prepared in Example 2 in N,N-dimethylacetamide, and maintaining the temperature at 0°C for reaction for 5.5 hours to obtain a polyamide-amic acid solution, wherein the molar ratio of pyromellitic anhydride, diphenyl ether diamine and the functional monomer prepared in Example 2 is 1:0.98:0.04, and the solid content of the polyamide-amic acid solution is 20%; Step S2, add acetic anhydride and triethylamine to the above-mentioned polyamide-amic acid solution and stir well, react at 30°C for 5h, and then after vacuum degassing and filtration treatment, spray out through a spinneret and enter the treatment liquid to obtain primary fibers, and then pass through a coagulation bath, hot water drawing, water washing, drying, thermal cyclization, and winding to obtain polyamide-imide composite nanofibers. The volume ratio of acetic anhydride and triethylamine is 2.5:1, and the molar ratio of acetic anhydride to the dianhydride monomer described in step S1 is 0.4:1. The treatment liquid is a mixed solution of acetic anhydride and triethylamine with a volume ratio of 1:3, and the coagulation bath is a mixed solution of N,N-dimethylacetamide and water with a volume ratio of 4:6. The hot water drawing temperature is 90°C, the drawing multiple is 2.4, and the thermal cyclization temperature is 320°C.
[0016] Example 6: A method for preparing polyamide-imide composite nanofibers, comprising the following steps: Step S1, mixing 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, diphenyl ether diamine and the functional monomer prepared in Example 3 in N,N-dimethylacetamide, and keeping the temperature at 0°C for 6 hours to obtain a polyamide-amic acid solution, wherein the molar ratio of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, diphenyl ether diamine and the functional monomer prepared in Example 3 is 1:0.96:0.05, and the solid content of the polyamide-amic acid solution is 25%; Step S2, add acetic anhydride and triethylamine to the above-mentioned polyamide-amic acid solution and stir well, react at 35°C for 6h, and then after vacuum degassing and filtration treatment, spray out through a spinneret and enter the treatment liquid to obtain primary fibers, and then pass through a coagulation bath, hot water drawing, water washing, drying, thermal cyclization, and winding to obtain polyamide-imide composite nanofibers. The volume ratio of acetic anhydride and triethylamine is 3:1, and the molar ratio of acetic anhydride to the dianhydride monomer described in step S1 is 0.5:1. The treatment liquid is a mixed solution of acetic anhydride and triethylamine with a volume ratio of 1:3, and the coagulation bath is a mixed solution of N,N-dimethylacetamide and water with a volume ratio of 4:6. The hot water drawing temperature is 90°C, the drawing multiple is 2.4, and the thermal cyclization temperature is 320°C.
[0017] Comparative Example 1: This comparative example is a polyamide-imide composite nanofiber, which differs from Example 6 in that p-phenylenediamine is used instead of the functional monomer prepared in Example 3, and the rest are the same.
[0018] Comparative Example 2: This comparative example is a polyamide-imide composite nanofiber, which differs from Example 6 in that amino-terminated silicone is used instead of the functional monomer prepared in Example 3, and the rest are the same.
[0019] Comparative Example 3: This comparative example is a polyamide-imide composite nanofiber, which is different from Example 6 in that the functional monomer prepared in Example 3 is not added, and the rest is the same.
[0020] The polyamide-imide composite nanofibers prepared in Examples 4-6 and Comparative Examples 1-3 were subjected to performance tests: Breaking strength test: According to GB / T 14344-2022 "Test method for tensile properties of chemical fiber filaments", the breaking strength of the fiber before high temperature treatment is tested, and then the fiber is subjected to a heat resistance test at a temperature of 300°C for 48 hours, and the breaking strength is tested, and the breaking strength retention rate is calculated; Elongation at break test: Single-filament strength test is carried out on the fully automatic single-fiber universal tester FAVIMAT+. The single-filament with a separation length of more than 20 mm is tested at an initial stress of 0.3 cN and a tensile speed of 10 mm / min. The test results are shown in Table 1: Table 1: Performance test results
[0021] It can be seen from Table 1 that the polyamide-imide composite nanofiber prepared in the present invention has excellent heat resistance, breaking strength and toughness through tests of heat resistance, breaking strength and breaking elongation.
[0022] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing polyamide-imide composite nanofibers, characterized in that: The method comprises the following steps: Step S1, mixing and stirring the dianhydride monomer, the diamine monomer and the functional monomer in an organic solvent, and maintaining the temperature at 0° C. for reaction for 5-6 hours to obtain a polyamide-amic acid solution; Step S2, adding acetic anhydride and triethylamine to the above polyamide-amic acid solution and stirring well, reacting at 25-35°C for 4-6h, and then subjecting to vacuum degassing and filtering treatment, spraying out through a spinneret and entering a treatment liquid to obtain primary fibers, and then subjecting to a coagulation bath, hot water drawing, water washing, drying, thermal cyclization, and winding to obtain polyamide-imide composite nanofibers; The functional monomer is obtained by reacting hydrogen-terminated polydimethylsiloxane with a double bond-benzamide derivative, the double bond-benzamide derivative is obtained by reacting an isocyanate-benzamide derivative with ethylenediamine, the isocyanate-benzamide derivative is obtained by reacting toluene-2,4-diisocyanate with an amino-benzamide derivative, the amino-benzamide derivative is obtained by reducing a nitro-benzamide derivative, and the nitro-benzamide derivative is obtained by reacting p-nitrobenzoyl chloride with 1-amino-5-hexene.
2. The method for preparing a polyamide-imide composite nanofiber according to claim 1, characterized in that: In step S1, the molar ratio of the dianhydride monomer, the diamine monomer and the functional monomer is 1:0.96-1:0.02-0.05, the solid content of the polyamide-amic acid solution is 15%-25%, the dianhydride monomer is one of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride or 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, the diamine monomer is one of p-phenylenediamine or diphenyl ether diamine, and the organic solvent is one of N,N-dimethylformamide or N,N-dimethylacetamide.
3. The method for preparing a polyamide-imide composite nanofiber according to claim 1, characterized in that: The volume ratio of acetic anhydride and triethylamine in step S2 is 2-3:1, the molar ratio of acetic anhydride and the dianhydride monomer in step S1 is 0.3-0.5:1, the treatment liquid is a mixed solution of acetic anhydride and triethylamine in a volume ratio of 1:3, the coagulation bath is a mixed solution of N,N-dimethylacetamide and water in a volume ratio of 4:6, the hot water drawing temperature is 90°C, the drawing multiple is 2.4, and the thermal cyclization temperature is 320°C.
4. The method for preparing a polyamide-imide composite nanofiber according to claim 1, characterized in that: The functional monomer is prepared by the following steps: Step A1, stir p-nitrobenzoyl chloride in tetrahydrofuran, transfer to an ice-water bath, add pyridine and stir for 1 hour, then add 1-amino-5-hexene and stir for 3.5-4.5 hours, add water and stir for 30 minutes, filter, recrystallize and dry to obtain a nitro-benzamide derivative; Step A2, stirring a nitro-benzamide derivative, ethanol and a catalyst Pt / SnO2-Sb2O3 at a constant temperature of 50°C for 15 minutes, then introducing 4MPa hydrogen, stirring for 3 hours, and extracting to obtain an amino-benzamide derivative; Step A3, toluene-2,4-diisocyanate, sodium hydroxide, toluene and amino-benzamide derivative are mixed, and the temperature is raised to 60-70° C., nitrogen is introduced to react for 10-15 hours, and rotary evaporation and drying are performed to obtain isocyanate-benzamide derivative; Step A4, adding sodium hydroxide, toluene and ethylenediamine to the isocyanate-benzamide derivative, stirring evenly, reacting under nitrogen at 70° C. for 6-8 hours, rotary evaporation and drying to obtain a double bond-benzamide derivative; Step A5: Under nitrogen conditions, the double bond-benzamide derivative, KARSTEDT catalyst and toluene are mixed and stirred evenly, and then hydrogen-terminated polydimethylsiloxane is slowly added dropwise, and the temperature is raised to 80-100° C. to react for 20-24 hours, and then rotary evaporated, purified and dried to obtain a functional monomer.
5. The method for preparing a polyamide-imide composite nanofiber according to claim 4, characterized in that: In step A1, the dosage ratio of p-nitrobenzoyl chloride, tetrahydrofuran, 1-amino-5-hexene, pyridine and water is 0.01-0.03 mol:100 mL:0.01-0.03 mol:0.01-0.03 mol:200 mL.
6. The method for preparing polyamide-imide composite nanofiber according to claim 4, characterized in that: Step A2, the usage ratio of nitro-benzamide derivative, ethanol and catalyst Pt / SnO2-Sb2O3 is 0.5-1.5g:10-30mL:0.3-0.9g, Pt in the catalyst Pt / SnO2-Sb2O3 accounts for 0.5wt% of the total catalyst, and the molar ratio of Sn to Sb is 0.1:
1.
7. The method for preparing polyamide-imide composite nanofiber according to claim 4, characterized in that: In step A3, the amount ratio of toluene-2,4-diisocyanate, sodium hydroxide, toluene and amino-benzamide derivative is 0.01-0.02 mol: 0.02-0.04 g: 100 mL: 0.01-0.02 mol.
8. The method for preparing polyamide-imide composite nanofiber according to claim 4, characterized in that: In step A4, the molar ratio of ethylenediamine to toluene-2,4-diisocyanate in step A3 is 1:1, and the amount of sodium hydroxide used is 0.015-0.03 g.
9. The method for preparing polyamide-imide composite nanofiber according to claim 4, characterized in that: Step A5, the molar ratio of hydrogen-terminated polydimethylsiloxane to the double bond-benzamide derivative is 1:1-1.02, and the KARSTEDT catalyst accounts for 0.002wt% of the total reactants.
10. A polyamide-imide composite nanofiber prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of polyamide-imide copolymer fibers
CN112251825A
Polymer based on p-phenylenediamine
CN113667126A
Polyimide fiber and method for preparing polyimide fiber
CN113818097A
Physical crosslinking type transparent nylon and preparation method thereof
CN119039581A
Ceramic sol nanohybrid materials using polydimethylsiloxane-polyamideimide copolymers and manufacturing method thereof
KR1020160146250A